Redesign UI/UX Website HSB Investasi Menggunakan Metode Design Thinking - Cut Ratna Komala; Hafid Setyo Hadi; Sari Setyaning Tyas (Penerbit Jurnal Indonesia, 2025)
The advancement of technology in the fields of finance and investment has encouraged companies such as HSB Investasi to offer digital services supported by advanced technological systems. This study aims to UI/UX of the HSB Investasi website through a redesign process. The development focused on aligning information and features between the website and mobile application, refining navigation structure, and enhancing information presentation to ensure better user comprehension. The applied method follows the Design Thinking approach, which includes stages such as problem identification, solution design, and interactive prototyping. Alignment between platforms was conducted to prevent user disorientation when accessing both services. A quantitative approach was employed using the SUS instrument, involving 30 respondents selected based on predetermined user segments. Initial evaluation of the previous website version yielded an average usability score of 63, which fell below the acceptable threshold. Following the redesign, the score significantly improved to 89, categorizing it as “excellent.” These findings indicate that improvements in design and cross-platform consistency contribute significantly to the optimization of user interaction comfort and clarity. The addition of onboarding features and a more intuitive navigation structure also helped new users better understand available functions. In conclusion, the implementation of the Design Thinking method proved effective in significantly enhancing the overall UI/UX quality of the HSB Investasi website.